Collaboration Model between Guidance Counselors and Homeroom Teachers in Guiding Students with Discipline Problems at MTSN 1 Ternate - Isti Saindra; Muhamad Taib Hi Bendar; Ria Hayati; Mawardi Djamaluiddin (Manunggal Halim Jaya, 2026)
Student discipline issues are a major challenge in the implementation of education in Islamic schools, and require comprehensive and sustainable management. This study aims to analyze the collaboration model between Guidance and Counseling (BK) teachers and homeroom teachers in guiding students with disciplinary problems at MTsN 1 Ternate. This study used a qualitative approach with a case study design. The research subjects included BK and homeroom teachers, the madrasah principal, and students experiencing disciplinary problems. Data were collected through in-depth interviews, observations, and documentation studies and analyzed using interactive thematic methods. The results showed that collaboration between BK and homeroom teachers has been functioning well, but is still semi-formal and not yet structured in a written collaboration model. The division of roles between BK teachers and homeroom teachers is formed in practice, with homeroom teachers acting as early detectors and daily discipline coaches, and BK teachers acting as assessors and primary mentors. Collaborative interventions tend to use restorative and persuasive approaches, which are considered more effective than punitive ones. The main obstacles to collaboration include limited time, teacher workload, and lack of collaboration SOPs. This study recommends developing a systematic and sustainable collaboration model to increase the effectiveness of handling student discipline problems in madrasas.